Determination of β-asarone in alcoholic beverages - Yabiku, Helena Yuco (1980)
In order to evalu a te the presence of calamus oil in alco ho lic beverages, a qua n ti ta tive de tcrminati on of i ts active principIe f3-asarone was p er Io rmed, by means of two diffcren t methods: fl uo rome t r ic and gas liquid ch roma tograph y, and accomplished with a tomic mass spect rophotcme tric a nalysis. In 56 sarriples of alcoh ol ic beverages of 18 different brands, only one demonstrated to be in higher coritcn t tha n th e permittcd limit of 1 ppm, de tc rmi ned by Europe Counci!. The f3-asarone contents varied from O ~o 4.96 p pm. It was suggested to employ the gas liquid chromatography technique as official method for determination of f3-asarone in alcoholic beverages, since it is more specif ic than fluo r ime tr ic me tho d.